Evidence of a reduction over time in the behavioral severity of autistic disorder diagnoses. Issue 1 (19th January 2017) - Whitehouse, Andrew J.O.; Cooper, Matthew N.; Bebbington, Keely; Alvares, Gail; Lin, Ashleigh; Wray, John; Glasson, Emma J.
Abstract : The increasing prevalence of Autism Spectrum Disorders (ASD) may in part be due to a shift in the diagnostic threshold that has led to individuals with a less severe behavioral phenotype receiving a clinical diagnosis. This study examined whether there were changes over time in the qualitative and quantitative phenotype of individuals who received the diagnosis of Autistic Disorder. Data were from a prospective register of new diagnoses in Western Australia ( n = 1252). From 2000 to 2006, we examined differences in both the percentage of newly diagnosed cases that met each criterion as well as severity ratings of the behaviors observed (not met, partially met, mild/moderate and extreme). Linear regression determined there was a statistically significant reduction from 2000 to 2006 in the percentage of new diagnoses meeting two of 12 criteria. There was also a reduction across the study period in the proportion of new cases rated as having extreme severity on six criteria. There was a reduction in the proportion of individuals with three or more criteria rated as extreme from 2000 (16.0%) to 2006 (1.6%), while percentage of new cases with no "extreme" rating on any criteria increased from 58.5% to 86.6% across the same period. This study provides the first clear evidence of a reduction over time in the behavioral severity of individuals diagnosed with Autistic Disorder during a period of stability in diagnostic criteria. A shift toward diagnosing individuals with less severe behavioral symptoms may have contributed to the increasing prevalence of Autistic Disorder diagnoses. Autism Res 2017, 10: 179–187 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.